2014
DOI: 10.1007/s10896-014-9600-y
|View full text |Cite
|
Sign up to set email alerts
|

Typologies of Violence Exposure and Cognitive Processing in Incarcerated Male Adolescents

Abstract: Incarcerated youth experience high rates of violence exposure (VE), cognitive processing (CP) deficits, and mental health (MH) problems. It is not clear whether VE combined with CP deficits are particularly salient risk factors for MH dysfunction. Male incarcerated youth offenders (n = 115) completed standardized self-reports of MH and VE. CP was measured with executive functioning tasks and academic assessments. Person-centered Ward’s Squared Euclidian Distance cluster analysis was used to examine unique patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…A national longitudinal survey of North American adolescents found that cognitive skills did not protect adolescent from committing severe aggression and violent acts in disadvanced conditions of poverty and community violence (Bellair and McNulty, 2010). Similarly, findings among incarcerated North American adolescents did not confirm the hypothesis that severe family violence would not be associated with mental health problems (e.g., depression, anxiety, and aggression) among detainees who show high cognitive processing skills (e.g., executivefunctioning, metacognition and behavioral regulation) (Perkins et al, 2014).…”
Section: Cognitive Skills and Mental Health In Stressmentioning
confidence: 93%
“…A national longitudinal survey of North American adolescents found that cognitive skills did not protect adolescent from committing severe aggression and violent acts in disadvanced conditions of poverty and community violence (Bellair and McNulty, 2010). Similarly, findings among incarcerated North American adolescents did not confirm the hypothesis that severe family violence would not be associated with mental health problems (e.g., depression, anxiety, and aggression) among detainees who show high cognitive processing skills (e.g., executivefunctioning, metacognition and behavioral regulation) (Perkins et al, 2014).…”
Section: Cognitive Skills and Mental Health In Stressmentioning
confidence: 93%
“…One of the most consistent results of research in this field is that adolescents who assault their parents have more often been victims of abuse in the family or have witnessed violent behavior between their parents than those who do not [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Any kind of exposure to intrafamily violence can affect the normal development of offspring [ 28 ], such that those who have experienced or observed such violence are more likely to develop different cognitive, emotional, and/or behavior problems in childhood and to manifest violence and antisocial behaviors in adolescence [ 29 , 30 , 31 ] and adulthood [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other cross-sectional studies have shown associations between childhood IPV exposure and executive dysfunction in incarcerated adolescents, who were at greatest risk for mental health problems when both IPV exposure and executive dysfunction were high (Perkins et al, 2012; Perkins et al, 2014). However, to date there are no known longitudinal studies investigating the specific relation between early childhood exposure to IPV and speeded control, and the mechanisms through which IPV may impact youths’ speeded control skills have not been delineated.…”
Section: The Effects Of Ipv On Children’s Executive Functioningmentioning
confidence: 97%
“…There is evidence that the heightened risk for ADHD among IPV-exposed children is mediated by impairments in speeded control abilities (Towe-Goodman et al, 2011), again underscoring the importance of minimizing environmental threats to neurocognitive development during the sensitive preschool years. Other cross-sectional studies have shown associations between childhood IPV exposure and executive dysfunction in incarcerated adolescents, who were at greatest risk for mental health problems when both IPV exposure and executive dysfunction were high (Perkins et al, 2012;Perkins et al, 2014). However, to date there are no known longitudinal studies investigating the specific relation between early childhood exposure to IPV and speeded control, and the mechanisms through which IPV may impact youths' speeded control skills have not been delineated.…”
Section: The Effects Of Ipv On Children's Executive Functioningmentioning
confidence: 99%